Pengembangan Keterampilan Mekatronika Siswa SMK Puger melalui Proyek ROV - Joessianto Eko Poetro; Fais Hamzah; Imam Sutrisno; Fahmi Umasangadji (Bulletin of Community Engagement, 2025)
Mastery of mechatronics skills is a key factor in enhancing the competitiveness of vocational high school (SMK) graduates, especially in the era of Industry 4.0. This study aims to develop the mechatronics skills of SMK Puger students through a Remotely Operated Vehicle (ROV) project. The method used in this research is a project-based learning approach, involving the design, assembly, and testing of the ROV directly by students. The results show that the implementation of this project improves students' understanding of electrical systems, microcontroller programming, and mechanical assembly skills. Furthermore, this project also enhances teamwork and problem-solving skills. Thus, the development of mechatronics skills through the ROV project can be an effective alternative in improving the quality of learning in vocational schools. This research makes several significant contributions to vocational education, particularly in enhancing students’ mechatronics competencies through a practical and innovative learning model. These findings suggest that integrating PjBL and technological innovation in vocational education is a viable and impactful method to enhance student learning outcomes and workforce readiness